Determinants of Municipal Solid Waste in Urban Zone of Baglung Municipality, Nepal - Regmi, Tejendra; Ghimire, Manisha; Shrestha, Suman Man (Journal of Institute of Science and Technology, 2021)
The studies on the solid waste generation and characterization with their relationships with different determinants are limited in Nepal which helps in the implementation of the solid waste management approach. This study is focused on the quantification of the municipal solid waste (MSW) generation rate and its characterization in the Baglung Municipality, Nepal. Factors affecting MSW generation with perceptions towards the MSW management were also evaluated through household survey. The study was carried out in the month of January 2021 in four wards of urban zone in the municipality. The average waste generation rate in 188 households (HHs), 20 institutions, and 20 commercial sites were 0.43 kg/c/d, 0.83 kg/institute/day and 2.75 kg/commercial site/day, respectively. The largest component, which accounted for about 74% household waste, 75% institutional waste and 52% commercial waste composed of organic waste. The analysis of variance (ANOVA) indicates a significant variation in between MSW generation rate with respect to household size and type of days. Regarding affordability of MSW management, most of the households can be able to afford service fee ranged from US 0.5 to 1.0 (55.38%). Most of the households dispose of solid waste in the municipal vehicle. From this study, the residents of the municipality are suggested to prepare compost manure at the source for the minimization of waste volume to be transported and disposed of. Higher production of recyclable MSW depicts there is a possibility of revenue generation and importance of MSW management in community mobilization in the municipality.